The Possibility of Promotion: How Race and Gender Predict Promotion Clarity for Associate Professors. Issue 5 (May 2019) - Kulp, Amanda M.; Wolf-Wendel, Lisa E.; Smith, Daryl G.
Background/Context: The research on promotion to full professor is sparse. Research that does exist has largely emerged from single campuses and studies conducted through disciplinary associations. Extant studies strongly suggest the presence of equity issues in advancement throughout the academic pipeline. Our study uses cross-institutional results to offer analysis of and potential solutions for the problem. Purpose/Objective/Research Question: We explore the extent to which tenured faculty members at four-year postsecondary institutions are clear about their prospects of being promoted to full professor and how their background characteristics, institutional characteristics, and satisfaction with various aspects of academic work predict their perceptions of promotion clarity. We are focused on whether cultural taxation in the form of heavy service and advis-ing—often associated with underrepresented minority faculty and women faculty—is a factor. We examine the influence of ideal-worker norms and work/family demands on perceptions of promotion clarity. Lastly, we focus on the structural elements of the academy to frame the topic, rather than focusing on individual agency. Population/Participants/Subjects: This study uses data from the Collaborative on Academic Careers in Higher Education (COACHE) survey, a large, national study of postsecondary faculty. Our sample consists of 3, 246 individuals who held full-time, tenured positions as associate professor at four-year institutions when they responded to the surveys between 2010 and 2012. The sample was roughly divided between males (54%) and females (46%), and most faculty were employed at research institutions (59%). The sample was predominantly White (82%). The characteristics of the associate professors in the sample are representative of the larger U.S. faculty population at the time of the survey. Research Design: This quantitative study uses descriptive statistics to examine patterns in promotion clarity across various demographic and institutional characteristics. We examine how satisfaction variables intersect with perceptions of promotion clarity for associate professors. Then we conduct a series of linear regression analyses to explore the influence of predictors on associate professors' sense of clarity about promotion. Conclusions/Recommendations: Being unclear about expectations of promotion to full professor is clearly of concern to faculty members at four-year universities in the United States, but it is especially of concern to women. Satisfaction with service is a very important variable in predicting perceptions of promotion clarity. For all associate professors, working at certain types of institutions or in particular academic disciplines had an inverse relationship with promotion clarity. The factors associated with lack of clarity about promotion are more structural than individual.